Effects of conductive curved partition and magnetic field on natural convection and entropy generation in an inclined cavity filled with nanofluid - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier, 2020)
In this study, natural convection and entropy generation analysis of nanofluid in an inclined cavity including a curved shaped conductive partition are performed under the impact of inclined magnetic field by using Galerkin weighted residual finite element method. Numerical simulations are performed for various values of Rayleigh number (between 10(4) and 10(6)), inclination angle of the cavity (between 0 degrees and 180 degrees), Hartmann number (between 0 and 50), orientation angle of the magnetic field (between 0 degrees and 90 degrees), curvatures of the conductive partition (between 0.01 and 0.1), conductivity ratio (between 0.01 and 100) and solid nanoparticle volume fraction (between 0 and 0.03). The average Nusselt number increases with higher values of Rayleigh number, inclusion of nano sized particles whereas it is reduced with higher values of Hartmann number. When the value of Hartmann number is increased from 0 to 50, 32% and 34% of average Nusselt number reduction is obtained for water and nanofluid. The cavity inclination angle has significant effects on the convective heat transfer characteristics. When the radii of the vertical and horizontal elliptic curved partitions are increased to 0.3H, 23% and 3.8% deterioration of average Nusselt number is obtained while significant enhancement in the heat transfer is observed when the conductivity of the partition is increased. The second law analysis was included in the study and entropy generation rate was found to vary with different parameters. Contributions of solid and fluid domains to the entropy generation rate were determined. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Curved partition; Entropy generation; Nanofluids; Magnetohydrodynamics; Inclined cavity